PLANNING PROFESSIONAL AND PERSONAL DEVELOPMENT OF SENIOR EXECUTIVES IN PUBLIC ADMINISTRATION - Orliv Mariana (Університети і лідерство, 2016)
This article explores conditions for ensuring efficiency of planning professional and personal development of senior executives in public administration, and offers a model taking into consideration the provisions of the new Law of Ukraine “On civil service”. Approaches to formulation of goals, strategy development and individual programs of development are analyzed. Models and methods of professional, leadership and other qualities of senior executives are examined, and specific features of their application are reviewed. A list of normative legal acts and methodical materials, the development of which will be aimed at ensuring the professionalization of the civil service, is offered.